Comparisons on growth performance, survivability, organoleptic qualities and economic feasibility of asian seabass (Lates calcarifer) reared in different salinities - Mohammed Noorfaiz Yusof,; Norfazreena Mohd Faudzi,; Nur Aziemah Jasni,; Elexson Nillian,; Senoo, Shigeharu; Fui, Fui Ching (Penerbit Universiti Kebangsaan Malaysia, 2024)
Asian seabass, Lates calcarifer is among the most cultured aquaculture species in the Southeast Asian region due to its remarkable tolerance for a diverse environmental fluctuation. In aquaculture, salinity has a direct influence on many biological, physiological and market value of any cultured fish. This study investigated the impacts of different salinities (0, 15, & 30 ppt) on Asian seabass growth, body indices, feeding performance, organoleptic qualities, and production cost for 85 days. Ninety fish were reared in 700-liter tanks equipped with recirculation system with 10 fish each tank. They were fed with commercial marine feed. The findings revealed Asian seabass in 15 ppt attained significantly higher (p>0.05) body weight (470.40 ± 41.16 g), total length (31.51 ± 0.81 cm), total feed intake (309.28 ± 35.66 g/fish) and daily feed intake (3.64 ± 0.42 g/fish/day) compared to 30 ppt but remained insignificant with 0 ppt. Meanwhile, there was no significant difference (p0.05) compared to 15 ppt but remained insignificant with 0 ppt. Economically, Asian seabass cultured in 15 ppt yielded the most optimal conditions for profitable production. The findings conclude 15 ppt can promotes enhanced growth performance and profitability, while 0 ppt and 30 ppt can promote consumer acceptance positively.